PENINGKATAN PRESTASI BELAJAR PAI TERHADAP PEMBELAJARAN KOOPERATIF TIPE TEAMS-GAMES-TOURNAMENT (TGT) PADA PESERTA DIDIK: Peningkatan, Prestasi, PAI dan TGT - Nureni, Nureni (Dahzain Nur, 2023)
This type of  research is classroom action research with the research subject being the fourth grade student og MI Abnaul Amir which consists of 16 students. The research was carried out in two action cycles. The first sysle discussed the subject of cooperatives and people’s welfare, while the second cycle discussed production, communication and transportation technology. Research data obtained from observations during science learning activities took place using student learning cooperation observation sheets, student response questionnaires,interviews, and documentation. The data obtained the student learning cooperation observation sheet and student response quetionnaires were analyzed by calculating the percentage of all observed aspects. The resultd showed thst the cooperative learning of students’ science cooperation after the teams games tournament (TGT) type cooperative learning model showed that on average all aspects learning collaboration of fourth grade stude students of MI Abnaul Amir. Namely in the first cycle of student learning cooperation (4.08) for the second cycle of (4.77%). In addition, the results of the questionnaire to student learning cooperation on learning cooperation on learning also increased by (32.14%) in the first cycle and by (42.28%) in the second cysle.